Incorporating employability in the EOP course - Jan, Zarina; Othman, Khairiah; Adam, Zalika (2010)
Employers, universities and professional bodies agree that Malaysia needs to develop professionals who are highly skilled and ready to face the challenges of increased competition. More than ever we need professionals who are responsive to economic, social, cultural, technical and environmental change and can work flexibly and intelligently across business contexts. The Malaysian industry requires new graduates who understand the part they play in building their organisations, and have the practical skills to work effectively in their roles. In line with this, a survey conducted by the Federation of Malaysian Manufacturers (FMM, 2007) among its members revealed that the top five difficulties in recruiting fresh graduates were; (1) lack of industrial training, (2) communication problems/weak command of English, (3) weak problem solving skills, (4) job hopping and (5) lack of self confidence. This paper investigates to see if the field trip activity, which is one of the components in the English for Specific Purpose (EOP) syllabus for Economics, Engineering and ICT final year students, can help graduates meet the requirements of the incumbent employment market. The main objective of this study is to show that it is imperative for all higher learning institutions to prepare students with strong communicative, interpersonal and problem solving skills before they go into the workplace. The methodology used in this study consists of pre and post survey questionnaires to investigate students’ preparation emotionally and physically before the field trip and their experience after the field trip. Findings from the research do not only indicate that students were more prepared and confident to face people in the workplace, but also made them realize the importance of mastering the English language to secure a place for themselves in employment.